Stres Kerja Ditinjau Dari Kecerdasan Emosi, Modal Psikologis dan Dukungan Sosial - Nur Pratiwi Noviati (Psikologika: Jurnal Pemikiran dan Penelitian Psikologi, 2015)
The aim of this research was to empirically examine the correlation between internal factors (emotional intelligence and psychological capital}, and external factor (social support) with work stress. The level of emotional intelligence, psychological capital and social support is inversely proportional to the work stress level. The respondents of this study consists of the employees who have the loads and more responsibilities at work. The number of respondents involved is a nurse at a private hospital in the province as many as 61 people, the crew (ABK) in the Port of Boom Baru Palembang as many as 88 people, and employees at Printing in Yogyakarta as many as 84 people. The measurement tool used is Emotional Intelligence Scale, Psychological Capital Scale, Social Support Scale and Work Stress Scale. Statistic method by SPSS for windows was applied to analyze data. Correlation test showed the results of emotional intelligence and work stress has a correlation coefficient r= -0792, p= 0.000 (p <0.01), psychological capital and job stress has a correlation coefficient r= -0.308, p= 0.011 (p <0.05), social support and work stress has a correlation coefficient r= -0.686, p= 0.000 (p <0.05). The test result showed a sigmificant negative correlation between internal factors and external factor with work stress. Then, the proposed hypothesis is accepted. Keywords: work stress, emotional intelligence, psychological capital, social support